GAYA BELAJAR SISWA DAN METODE MENGAJAR GURU SMA NEGERI 1 HILIRAN GUMANTI - Desi Lailatul Husna; Syafri Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe students' learning styles and teachers' teaching methods at SMA Negeri 1 Hiliran Gumanti. The background of this research is based on the importance of understanding students' learning styles in supporting the effectiveness of the learning process. The research used a descriptive quantitative approach with a questionnaire instrument filled out by 50 students in grades X and XI. The results showed that auditory learning style is the most dominant learning style, both in class X (24%) and class XI (25%), followed by visual and kinesthetic learning styles. However, the teacher's teaching method still tends to be lecture-based and has not accommodated variations in students' learning styles. This finding indicates the need for the application of varied, multimodal and differentiated learning models to improve student engagement and learning outcomes. Recommendations are addressed to teachers to adjust teaching strategies based on students' learning style tendencies in accordance with the principles of Merdeka Curriculum.